Cultivating Pearls of Wisdom: Creating Protected Niche Spaces for Inner Transformations amidst the Metacrisis - Kira Jade Cooper; Don G. McIntyre; Dan McCarthy (Challenges, 2024)
The impetus for this paper emerges from the growing interest in leveraging inner transformations to support a global shift in ways of seeing and being. We caution that without sufficient individual and systemic maturity, inner transformations will be unable to hold the whole story and that attempts to drive paradigmatic shifts in ill-prepared systems will lead to insidious harms. As such, interventions for inner change will not have sufficient protected niche space to move beyond the boundaries of best practices towards wise practices. Drawing on Indigenous trans-systemics, we offer the metaphor of pearls as an invitation to recontextualize how inner transformations are conceived and approached in the metacrisis. To further develop this notion, we share a story of Wendigo and Moloch as a precautionary tale for the blind pursuit of inner and outer development. Weaving together metaphor, story, and scientific inquiry, we bring together Anishinaabe and Western knowledge systems for the purposes of healing and transformation. We hope that this paper will create space for wise practices—gifts from Creator to help sustain both Self and the World—to emerge, establish, and flourish. We invite readers on an exploration into the whole system of systems that are endemic to Anishinaabe cosmology, and a journey of reimagining new stories for collective flourishing amidst the metacrisis.